1968
DOI: 10.1083/jcb.38.1.202
|View full text |Cite
|
Sign up to set email alerts
|

The Ultrastructure of the M Line in Skeletal Muscle

Abstract: By electron microscopy, the ultrastructure of the M line was investigated in fibers from frog nonglycerinated semitendinosus muscles at body length and at different degrees of shortening and stretch. The M line appeared as a line of high electron opacity in the middle of the A band. Its framework consists of: (i) three (four or five) arrays of transverse M bridges, 200 A apart, connecting each A filament with its six neighbors; (ii) M filaments, parallel to the A filaments, passing through the M line and linki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
52
0

Year Published

1978
1978
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(56 citation statements)
references
References 16 publications
4
52
0
Order By: Relevance
“…Knappeis and Carlsen (1962) observed that I-filaments in longitudinal sections terminate as rod-like projections on either side of the Z-disk with an I-filament on one side of the Z-disk lying between two I-filaments on the opposite side (see Figure 1). Thus, I-filaments are not continuous through the Z-disk.…”
Section: Z-disk Ultrastructurementioning
confidence: 99%
See 4 more Smart Citations
“…Knappeis and Carlsen (1962) observed that I-filaments in longitudinal sections terminate as rod-like projections on either side of the Z-disk with an I-filament on one side of the Z-disk lying between two I-filaments on the opposite side (see Figure 1). Thus, I-filaments are not continuous through the Z-disk.…”
Section: Z-disk Ultrastructurementioning
confidence: 99%
“…A, whereas the ostensible diameter of the Z-filaments is 50 -7 A. Con sequently, one of the principal criticisms of the Knappeis and Carlsen (1962) model has now been mitigated, and it seems quite likely that the thin fila ment may indeed split into two or perhaps more smaller filaments as it enters the Z-disk. Reedy (1964) described che scruccure in transverse sections of Z-disk from rat striated muscle as having a "basketweave" appearance.…”
Section: Z-disk Ultrastructurementioning
confidence: 99%
See 3 more Smart Citations